Subacute liver failure caused by hyperthyroidism and complicated by drugs: a case report and review of the literature - Hou, Yiwei; Tong, Mingxu; Yang, Yu; Zhou, Zijun; Fu, Yunxi; Gou, Zhennian; Xi, Jinting; Liao, Xiangyu; Li, Shixin; Zhu, Wufei (Frontiers in Medicine, 2025)
BackgroundSevere liver dysfunction due to concurrent hyperthyroidism and drug-induced liver injury (DILI) is exceedingly rare, posing significant diagnostic and therapeutic challenges. This case report highlights the complexity of managing simultaneous hepatic injuries caused by hyperthyroidism itself and the hepatotoxic effects of antithyroid medications. Such dual etiologies necessitate careful clinical evaluation and innovative treatment approaches, including artificial liver sup89 port.Case summaryA 34-years-old male presented with progressive weight loss for 1 year and severe jaundice for 1 month. He had previously been diagnosed with hyperthyroidism and treated intermittently with methimazole and propranolol. Upon admission, laboratory evaluations revealed markedly elevated liver enzymes and bilirubin (ALT 255 U/L, AST 109 U/L, total bilirubin 697.55 μmol/L). His thyroid function was severely impaired (TSH 0.012 μIU/mL, FT3 > 30.8 pmol/L, FT4 > 154.8 pmol/L). The patient underwent multidisciplinary management, including glucocorticoids, plasma exchange, and bilirubin adsorption therapy. Despite multiple therapeutic interventions, his clinical status fluctuated significantly. The decision to discontinue antithyroid medications due to exacerbating liver injury complicated the hyperthyroidism management further. Eventually, treatment with radioactive iodine was successfully implemented, resulting in stabilized thyroid and liver function.ConclusionClinicians must consider overlapping etiologies of liver injury in hyperthyroid patients and employ multidisciplinary approaches for effective management.